Performance evaluation of real time control in urban wastewater systems in practice: Review and perspective. (September 2017) - van Daal, Petra; Gruber, Günter; Langeveld, Jeroen; Muschalla, Dirk; Clemens, François
Abstract: Real time control (RTC) is generally viewed as a viable method for optimising the performance of urban wastewater systems. A literature review on the performance evaluation of RTC demonstrated a lack of consensus on how to do this. Two main deficiencies were identified: omitting uncertainty analysis and applying limited evaluation periods. A general methodology to evaluate the performance of RTC in practice, that takes into account these deficiencies, is proposed. The methodology is either data or model driven and the (dis)advantages of each are discussed. In a case study for a combined sewer system with limited discharge to a WWTP, it is demonstrated that the successful application of RTC and the possibility to determine a significant effect is very much dependent on the goal. It also clearly illustrates the need for taking uncertainties into account and that careful consideration in the chosen evaluation period is required. Highlights: In literature no consensus on evaluation of RTC in urban wastewater systems exist. Main deficiencies are lack of uncertainty analysis and too short evaluation periods. A methodology is proposed for the performance evaluation of RTC in practice. (Dis)advantages of a data or model driven evaluation are discussed. The need for uncertainty analysis and a proper evaluation period is demonstrated.